Dietary patterns associated hyperuricemia among Chinese aged 45 to 59 years: An observational study. Issue 50 (December 2017) - He, Fang; Wang, Lei-Lei; Yu, Xiao-Long
Abstract : Abstract: In our literature research, we have not found any study reporting the association between the major dietary patterns and the risk of hyperuricemia in a middle-aged Chinese population. Herein, the present study aimed to evaluate the association of dietary patterns with the risk of hyperuricemia in the city of Hangzhou, Zhejiang Province, East China. We included 1204 participants (743 males and 461 females) aged 45 to 59 years in the present cross-sectional study. Dietary intake was assessed using a semiquantitative food frequency questionnaire in 2014 to 2016. All biochemical data and anthropometric measurements were collected following standardized procedures. Dietary patterns were determined by using factor analysis. We examined the associations between major dietary patterns and hyperuricemia risk by log-binominal regression analysis, and the results are presented as prevalence ratio (PR) and confidence interval (CI). Three major dietary patterns were identified by means of factor analysis: traditional Chinese, meat food, and mixed food patterns. After controlling for potential confounders, subjects in the highest quartile of the traditional Chinese pattern scores had a lower PR for hyperuricemia (PR = 0.82; 95%CI: 0.426–0.922), in comparison to those from the lowest quartile, while compared with the lowest quartile of the meat food pattern, the highest quartile had a greater PR for hyperuricemia (PR = 1.48; 95%CI: 1.120–2.097). Besides, no association was observed between mixed food pattern and the risk of hyperuricemia. Our findings indicate that the traditional Chinese pattern is associated with a decreased risk of hyperuricemia, and the meat food pattern is associated with an increased risk of hyperuricemia, whereas the mixed food pattern shows no association with the risk of hyperuricemia. Further large prospective studies are warranted to confirm our findings.